Infusion line contamination in preterm neonates: impact of infusion line design, length, and use duration: the multicenter ChronoBIOline study - Dos Santos, Sandra; Valentin, Anne-Sophie; Farizon, Mathilde; Charbonneau, Manon; Boukhris, Mohamed Riadh; Brat, Roselyne; Cazzorla, Fabiana; Chauvel, Jennifer; Cneude, Fabrice; Coutable, Pauline; Demasure, Maryvonne; Duminil, Emeline; et al. (Frontiers in Microbiology, 2025)
IntroductionCentral venous catheters are critical in preterm neonatal care but increase the risk of central line-associated bloodstream infections (CLABSIs). The incidence of S. haemolyticus-associated CLABSIs in French neonates is increasing, but the mechanisms underlying this trend remain unclear.MethodsWe examined microorganisms in 108 central line infusion sets used in preterm infants across 12 neonatal intensive care units, and collected at the time of removal.ResultsThe infusion sets varied widely in type (28 types; 1-6 parts) and length (10-180 cm, mean 52.9 cm). Contamination was detected in 24 infusion sets (22.2%), mainly by coagulase-negative Staphylococci (50.0%) and Bacillus species (41.7%). Higher contamination rates were linked to longer infusion lines (> 50 cm; p < 0.001), usage beyond 7 days (p = 0.002), and multi-line infusion systems (p < 0.001).DiscussionOur findings are fully consistent with guidelines, which recommend simpler designs and a 4 or 7-day use of infusion sets, emphasizing the importance of adhering to these guidelines to reduce the risk of CLABSIs. Additionally, our findings raise concerns regarding the use of multi-line infusion systems. These devices, which combine extended infusion line length, manufacturer-authorized use of up to 21 days, and intermittent use of certain infusion lines, are easily contaminated during use, creating a high-risk situation for central line contamination.